BLACKENING OF CANNED PRAWN AND ITS PREVENTION - . NANDAKUMARAN, M; CHAUDHURI, D. R. CHAUDHURI; PILLAI, V K (Fishery Technology, 2025)
The paper gives an account of the types of blackeningassociated with canned prawn in brine and their control. It wasfound that blackening caused by iron sulphide could be controlledb):' maintaining proper titratable acidity of fill brine in cans. Thepaper also elaborates on the factors responsible for or governing thiscriticaltitratable acidity. In regard to copper sulphide blackening,control was found to be difficult by maintaining the acidity or Â·byadditives such as EDTA when the copper content in the materialwent above the critical level.